Variação espacial e temporal em ocupação de aves em floresta de terra firme da Amazônia Central - Watzel, Stéphany (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
Variation in occupancy of birds in a terra firme forest from Central Amazon. Population dynamics of species has been the focus of ecological studies for many years. Understanding this process is relevant to describe natural patterns. Ideally, it would be necessary to know all the species, but the immense biological diversity within Amazon makes it an unrealistic task. In this context, recognizing patterns can be helpful. Seeking to answer whether categorizations based on natural history characteristics of forest birds can be used to understand temporal and spatial patterns of occupancy, we tested hypotheses about differences in occupancy and turnover to 58 species classified a priori into four functional groups (frugivores, insectivores understory, insectivorous army ant-following and frugivores with the reproductive system in lek). Data were collected between 2005 and 2008 by the Project TEAM (Tropical Ecology, Assessment and Monitoring) in three areas of primary terra firme forest north of Manaus. We considered the heterogeneity that may occur in primary forests and found that for some species the occurrence was different among the studied areas. Eleven species showed significant temporal variation. Our results showed that 11 species of understory insectivores are more sensitive to local effects from the study areas. Frugivorous and army ant-following varied widely as the estimates of occupancy and turnover rate. Frugivores with lek, in general, had the lowest estimates of occupancy. Despite some observed trends, we did not find strong effects of the functional groups used in the study. The data reinforces the notion that spatial effects are more important than temporal effects for species occupancy.
Keywords: Aves; Floresta primária; Guildas